Themed issue on 2D materials. Issue 43 (27th October 2017) - Chhowalla, Manish; Lin, Zhong; Terrones, Mauricio
Abstract : Guest editors Manish Chhowalla, Zhong Lin and Mauricio Terrones introduce this Journal of Materials Chemistry C themed issue on 2D materials.